Early-Time Excited-State Relaxation Dynamics of Iridium Compounds: Distinct Roles of Electron and Hole Transfer - Liu, Xiang-Yang; Zhang, Ya-Hui; Fang, Wei-Hai; Cui, Ganglong (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2018)
Excited-state and photophysical properties of Ir-containing complexes have been extensively studied because of their potential applications as organic light-emitting diode emitting materials. However, their early time excited-state relaxation dynamics are less explored computationally. Herein we have employed our recently implemented TDDFT-based generalized surface-hopping dynamics method to simulate excited-state relaxation dynamics of three Ir(III) compounds having distinct ligands. According to our multistate dynamics simulations including five excited singlet states i.e., S n (n = 1–5) and ten excited triplet states, i.e., T n (n = 1–10), we have found that the intersystem crossing (ISC) processes from the S n to T n are very efficient and ultrafast in these three Ir(III) compounds. The corresponding ISC rates are estimated to be 65, 81, and 140 fs, which are reasonably close to the experimentally measured ca. 80, 80, and 110 fs. In addition, the internal conversion (IC) processes within respective singlet and triplet manifolds are also ultrafast. These ultrafast IC and ISC processes are caused by large nonadiabatic and spin–orbit couplings, respectively, as well as small energy gaps. Importantly, although these Ir(III) complexes share similar macroscopic phenomena, i.e., ultrafast IC and ISC, their microscopic excited-state relaxation mechanism and dynamics are qualitatively distinct. Specifically, the dynamical behaviors of electron and hole and their roles are variational in modulating the excited-state relaxation dynamics of these Ir(III) compounds. In other words, the electronic properties of the ligands that are coordinated with the central Ir(III) atom play important roles in regulating the microscopic excited-state relaxation dynamics. These gained insights could be useful for rationally designing Ir(III) compounds with excellent photoluminescence.